Estrés por sequía en Lupinus elegans procedentes de diferentes altitudes - Soto-Correa, José Carmen; Sáenz-Romero, Cuauhtémoc; Horacio, Horacio; Lindig-Cisneros, Roberto (Instituto de Ecología, A.C., 2015)
Drought stress in provenances of Lupinus elegans from different altitudesThe response of plants to altitudinal gradients depends on several factors and might differ among life strategies. Understanding these responses is highly relevant for management of forest species, particularly under climate change scenarios. We explored the response to drought of different provenances of Lupinus elegans, obtained from an altitudinal gradient. This species is a shrub that acts as a nurse plant in temperate forests in its geographical range. Seeds were collected from five natural provenances across an altitudinal gradient (2312 m to 2885 m a.s.l.). A common-garden experiment was conducted with four drought treatments (irrigation at every 3, 7, 15 and 21 days) in a shade-house located at 1972 m a.s.l. All provenances presented reduced heights and numbers of leaves with increased drought intensity, regardless of site of origin. Survival among provenances presented an altitudinal pattern, where those belonging to higher sites exhibited greater survival. Provenances from lower altitudes, coming from drier and warmer sites, exhibited poorer survival against drought stress. Overall, our results indicate that there are differences among provenances, but since this species is a short lived perennial (five years on average), it is more sensitive to microclimate than to conditions determined for large scale patterns such as altitudinal gradients. This should be considered for management practices such as ecological restoration.